COVID 19 - PROTECTING BANKS FROM BANKRUPTCY IN THE ARAB COUNTRIES (A COMPARATIVE STUDY) - Dr. Zubaida Abdul HadiAtim, (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Banks have an effective role in facilitating economic transactions, financial dealings and investment of funds and thus they are considered as pillars of the national economy. Therefore, banks may be affected in achieving their financial and investment objectives by national or international economic, social or health phenomena. Therefore, this research aimed to identify the precautionary measures that aimed to protect Banks from bankruptcy in the face of the effects of the spread of the Corona virus, in the Arab countries. The article followed the descriptive, analytical, and comparative approach. The study concluded with the most important results of which are that central banks in Arab countries have issued precautionary decisions and measures to protect banks and their customers from the effects of the epidemic. This was a reason to protect banks from bankruptcy and financial stability.